Myo1f, an Unconventional Long-Tailed Myosin, Is a New Partner for the Adaptor 3BP2 Involved in Mast Cell Migration - Navinés-Ferrer, Arnau; Ainsua-Enrich, Erola; Serrano-Candelas, Eva; Sayós, Joan; Martin, Margarita (Frontiers in Immunology, 2019)
Mast cell chemotaxis is essential for cell recruitment to target tissues, where these cells play an important role in adaptive and innate immunity. Stem cell factor (SCF) is a major chemoattractant for mast cells. SCF binds to the KIT receptor, thereby triggering tyrosine phosphorylation in the cytoplasmic domain and resulting in docking sites for SH2 domain-containing molecules, such as Lyn and Fyn, and the subsequent activation of the small GTPases Rac that are responsible for cytoskeletal reorganization and mast cell migration. In previous works we have reported the role of 3BP2, an adaptor molecule, in mast cells. 3BP2 silencing reduces FcRI-dependent degranulation, by targeting Lyn and Syk phosphorylation, as well as SCF-dependent cell survival. This study examines its role in SCF-dependent migration and reveals that 3BP2 silencing in human mast cell line (LAD2) impairs cell migration due to SCF and IgE. In that context we found that 3BP2 silencing decreases Rac-2 and Cdc42 GTPase activity. Furthermore, we identified Myo1f, an unconventional type-I myosin, as a new partner for 3BP2. This protein, whose functions have been described as critical for neutrophil migration, remained elusive in mast cells. Myo1f is expressed in mast cells and colocalizes with cortical actin ring. Interestingly, Myo1f-3BP2 interaction is modulated by KIT signaling. Moreover, SCF dependent adhesion and migration through fibronectin is decreased after Myo1f silencing. Furthermore, Myo1f silencing leads to downregulation of β1 and β7 integrins on the mast cell membrane. Overall, Myo1f is a new 3BP2 ligand that connects the adaptor to actin cytoskeleton and both molecules are involved in SCF dependent mast cell migration.